For Every to There Is a fro: Interpreting Time, Rhythm, and Gesture in Play. (November 2014) - McDonald, Peter
This essay looks at the nexus of rhythm, gesture, and time to argue that play has a systematicity of its own, separate from that of games, which rarely comes to our attention. It constructs a genealogy by following the idea of a to-and-fro motion characterizing play through Huizinga's Homo Ludens, to Gadamer's Truth and Method, and finally to Nicolas Abraham's essays on the phenomenology of rhythm. By looking at play as a selection of game acts, it is understood as having a style of its own that opens it up to microanalysis and interpretation. By opening up new rhythms and new ways of comporting one's body, play is understood to have a radical connection with the experience of time, and the analysis ends with some speculation on the nature of their relation.